The Impact of Earnings per Share and Debt to Equity Ratio Towards the Profitability of Companies Listed in LQ45 from 2009 to 2013 - Utzanah, Ashifa Arief; Murtaqi, Isrochmani (Journal of Business and Management, 2015)
Abstract- The aims of a firm to operate are the development and the continuity of the business itself. It can be achieved by gaining more profits for the firm. Profitability measures the company performance by comparing the profits of the company with its resources during the period year. The firm with high profitability shows that the company efficiently and productively manages the sales, assets, and investment in its operating activity to gain profit. This research objective is to find out the impact of earning per share, debt to equity ratio, and current ratio toward the profitability, which is indicated to return on assets, of the companies listed LQ45 index. The method use to analyze the impact is multiple linear regression. The sample used of this research is 22 companies that listed consistently on LQ45 Index during 2009 Ã¢â‚¬â€œ 2013 period. The result of this research shows that earning per share, debt to equity ratio, and current ratio have significant impact towards profitability (ROA). Earning per share has a positive significant impact towards profitability (ROA), on the other hand debt to equity ratio has a negative significant impact towards profitability (ROA), and current ratio also has a negative significant impact towards profitability (ROA). The earning per share, debt to equity ratio, and current ratio is influencing profitability (ROA) by 38.0%, as a result of Coefficient of Determination.Ã‚Â Keywords: earning per share, debt to equity ratio, current ratio, return on assets, multiple linear regression